Bottom-up direct writing approach for controlled fabrication of WS2/MoS2 heterostructure systems. Issue 71 (13th July 2016) - Dong, Rui; Moore, Logan; Aripova, Nozima; Williamson, Christopher; Schurz, Robert; Liu, Yuzi; Ocola, Leonidas E.; Kuljanishvili, Irma
Abstract : We demonstrate a scalable production of quality WS2 /MoS2 vertical and lateral heterostructures with controlled geometries employing a bottom-up direct writing approach. Abstract : The ability to construct heterostructures that consist of layered transition metal dichalcogenides materials (MX2 ) in a controlled fashion provides an attractive solution for materials design and device applications. For nanotechnology applications it is important to control the shape, geometry and precise position of the grown heterostructure assemblies on a variety of substrates. In this study, we developed a "direct writing" technique to fabricate arrays of WS2 /MoS2 and MoS2 /WS2 /MoS2 heterostructures at predefined locations on a silicon substrate in a controlled fashion. Water based precursor inks were implemented to ensure the formation of quality heterostructure surfaces which are free of residual polymer contaminants. With this technique we demonstrate an attractive and scalable technology with unique capabilities for precise growth of dissimilar MX2 materials, layered either in a vertical or lateral arrangement.